2008
DOI: 10.1093/hmg/ddn024
|View full text |Cite
|
Sign up to set email alerts
|

Loss of RB1 induces non-proliferative retinoma: increasing genomic instability correlates with progression to retinoblastoma

Abstract: Retinoblastoma clinical observations revealed the role of tumor suppressor genes in human cancer, Knudson's 'two-hit' model of cancer induction. We now demonstrate that loss of both RB1 tumor suppressor gene alleles initiates quiescent RB1(-/-) retinomas with low level genomic instability and high expression of the senescence-associated proteins p16(INK4a) and p130. Although retinomas can remain unchanged throughout life, highly proliferative, clonal and aneuploid retinoblastomas commonly emerge, exhibiting al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
278
1
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 296 publications
(294 citation statements)
references
References 42 publications
11
278
1
4
Order By: Relevance
“…Bland tumors composed entirely of photoreceptor differentiation called retinomas or retinocytomas are thought to be precursors of retinoblastoma. 48 Foci of photoreceptor differentiation observed in the basal part of endophytic retinoblastomas provides evidence for this hypothesis. 56 Untreated retinoblastoma is almost universally fatal.…”
Section: Retinoblastomamentioning
confidence: 85%
See 1 more Smart Citation
“…Bland tumors composed entirely of photoreceptor differentiation called retinomas or retinocytomas are thought to be precursors of retinoblastoma. 48 Foci of photoreceptor differentiation observed in the basal part of endophytic retinoblastomas provides evidence for this hypothesis. 56 Untreated retinoblastoma is almost universally fatal.…”
Section: Retinoblastomamentioning
confidence: 85%
“…Dimaras et al 48 have shown that both copies of the RB1 gene are also lost or inactivated in well-differentiated, benignly-behaving precursor tumors called retinomas or retinocytomas, which typically exhibits advanced degrees of photoreceptor differentiation (fleurettes). A number of additional mutations are required for malignant transformation into retinoblastoma.…”
Section: Retinoblastomamentioning
confidence: 99%
“…RB is a central regulator of proliferation that acts to inhibit E2F transcription factors through direct inhibition and through recruitment of chromatin-modifying enzymes (3). Recent evidence suggests that human retinoblastoma may be derived from a benign lesion, retinoma, caused by RB inactivation (4). Indeed, nonproliferative retinoma, but not retinoblastoma, was correlated with high levels of the RB family member p130, suggesting that, in the absence of RB, other family members can enforce cell cycle exit and inhibit tumorigenesis (4).…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence suggests that human retinoblastoma may be derived from a benign lesion, retinoma, caused by RB inactivation (4). Indeed, nonproliferative retinoma, but not retinoblastoma, was correlated with high levels of the RB family member p130, suggesting that, in the absence of RB, other family members can enforce cell cycle exit and inhibit tumorigenesis (4). Studies of retinoma using human samples are limited in that retinomas can only be examined in cases in which late-stage retinoblastoma leads to removal of the eye.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, amplification of MdmX has been shown to suppress p53-mediated cell death in retinoblasts lacking RB1 and to promote their clonal cell proliferation (83). KIF14, a putative oncogene and regulator of mitosis, is another candidate gene located in the amplified region of chromosome 1 (97,98). The expression of KIF14 is higher than that of MDMX in retinoma and RB samples, and expression of this gene is more frequently elevated (99).…”
Section: Associated Chromosomal Alterations In Rbmentioning
confidence: 99%